α-Synuclein emulsifies TDP-43 prion-like domain—RNA liquid droplets to promote heterotypic amyloid fibrils - Shailendra Dhakal; Malay Mondal; Azin Mirzazadeh; Siddhartha Banerjee; Ayanjeet Ghosh; Vijayaraghavan Rangachari (Communications Biology, 2023)
Abstract Many neurodegenerative diseases including frontotemporal lobar degeneration (FTLD), Lewy body disease (LBD), multiple system atrophy (MSA), etc., show colocalized deposits of TDP-43 and α-synuclein (αS) aggregates. To understand whether these colocalizations are driven by specific molecular interactions between the two proteins, we previously showed that the prion-like C-terminal domain of TDP-43 (TDP-43PrLD) and αS synergistically interact to form neurotoxic heterotypic amyloids in homogeneous buffer conditions. However, it remains unclear if αS can modulate TDP-43 present within liquid droplets and biomolecular condensates called stress granules (SGs). Here, using cell culture and in vitro TDP-43PrLD – RNA liquid droplets as models along with microscopy, nanoscale AFM-IR spectroscopy, and biophysical analyses, we uncover the interactions of αS with phase-separated droplets. We learn that αS acts as a Pickering agent by forming clusters on the surface of TDP-43PrLD – RNA droplets. The aggregates of αS on these clusters emulsify the droplets by nucleating the formation of heterotypic TDP-43PrLD amyloid fibrils, structures of which are distinct from those derived from homogenous solutions. Together, these results reveal an intriguing property of αS to act as a Pickering agent while interacting with SGs and unmask the hitherto unknown role of αS in modulating TDP-43 proteinopathies.